Диагностика нанопорошков и наноматериалов: учебное пособие - Ильин А. П. Александр Петрович; Коршунов А. В. Андрей Владимирович; Перевезенцева Д. О. Дарья Олеговна; Роот Л. О. Людмила Олеговна (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана